Convolutional Fine-Tuned Threshold Adaboost approach for effectual content-based image retrieval - Cep, Robert; Elangovan, Muniyandy; Ramesh, Janjhyam Venkata Naga; Chohan, Mandeep Kaur; Verma, Amit (Scientific reports, 2025)
Applications for content-based image retrieval (CBIR) are found in a wide range of industries, including e-commerce, multimedia, and healthcare. CBIR is essential for organising and obtaining visual data from massive databases. Traditional techniques frequently fail to extract high-level, relevant information from images, producing retrieval results that are not ideal. This research introduces a novel Convolutional Fine-Tuned Threshold Adaboost (CFTAB) approach that integrates deep learning and machine learning techniques to enhance CBIR performance. This dataset comprises image-based data collected from multiple sources. This image data were pre-processed using Adaptive Histogram Equalization (AHE). The features of localized image data were extracted using VGG16. For an efficient CBIR process, a novel CFTAB approach was introduced. It combines both deep and machine learning (ML) methods in the proposed architecture to improve the excellence of image search. To further improve performance, CFTAB incorporates an improved AB algorithm. This algorithm adjusts the threshold levels dynamically within a robust classifier to optimize training outcomes.
Keywords: VGG-16; High-level information; Deep and machine learning (DL, ML); Convolutional Fine-Tuned Threshold Adaboost (CFTAB); Content-based image retrieval (CBIR)